Pengaruh Indikator Ekonomi Makro, Kinerja Keuangan Perusahaan, Dan Risiko Sistematis terhadap Harga Saham - Hellen Tiara Fatrin; Ratnawati Kurnia (Ultima Accounting : Jurnal Ilmu Akuntansi, 2012)
The objective of this research is to examine the effect of macroeconomic factors, financial performance and also systematic risk partially and simultaneously toward stock price. The macroeconomic factors are proxied by inflation and Bank Indonesia interest rate, company financial performance are proxied by Price Earning Ratio (PER), Earning per Share (EPS), Return on Asset (ROA), and Return on Equity (ROE), and also systematic risk is proxied by beta. The object of this study are companies which have listed in Indeks LQ-45 in period 2007-2011. The samples are 11 companies determined based on purposive sampling. Data used in this study is secondary data such as financial statements, annual reports, inflation rate, Bank Indonesia interest rate, and stock price. The results of this study are (1) macroeconomic factor proxied by inflation does not have partial significant effect to stock price (2) macroeconomic factor proxied by Bank Indonesia interest rate does not have partial significant effect to stock price (3) company financial performance proxied by Price Earning Ratio has partial significant effect to stock price (4) company financial performance proxied by Earning per Share has partial significant effect to stock price (5) company financial performance proxied by Return on Asset does not have partial significant effect to stock price (6) company financial performance proxied by Return on Equity does not have partial significant effect to stock price (7) systematic risk proxied by Beta does not have partial significant effect to stock price (8) macroeconomic factors,company financial performances, and systematic risk have simultaneous significant effect to stock price. Keywords: macroeconomic factor, financial performance, systematic risk, inflation, Bank Indonesia interest rate, Price Earning Ratio (PER), Earning per Share (EPS), Return on Asset (ROA), and Return on Equity (ROE), beta, stock price.